Feasibility Study of Precision Longevity as an Innovation in Locus Medical Hub Services - Achmad Subahtiyar; Pipit Festi Wiliyanarti; Mundakir; Agus Chairul Anab (PROCEEDING UMSURABAYA, 2026)
Advances in healthcare technology and the growing public demand for personalized, preventive, and technology-based services are driving the transformation of modern healthcare models. One emerging concept is the medical hub, an integrated outpatient specialty care center that combines various medical services into a single comprehensive system. The integration of precision medicine, longevity medicine, and multidisciplinary care is becoming an increasingly common approach to support disease prevention and improve quality of life.This study aims to develop a model for an Integrated Precision and Longevity Medical Center at the Locus Medical Hub Clinic as an innovation in precision medicine-based healthcare services. The study employed a descriptive approach through literature review, health service needs analysis, and a review of the concept of modern medical service integration. The developed model includes a precision diagnostic unit, a longevity and healthy aging unit, a regenerative medicine unit, a lifestyle medicine unit, and a multidisciplinary complex case clinic. The results indicate that the proposed model has the potential to enhance healthcare service effectiveness through precision diagnostics, a multidisciplinary approach, and chronic disease prevention strategies. In addition, the model may improve service efficiency through collaboration among specialists and the utilization of modern health technologies. The Integrated Precision and Longevity Medical Center model has the potential to become an innovative, integrated, and adaptive healthcare service model that responds to advances in medical technology and future healthcare needs.